Learning to teach in times of the COVID-19 pandemic: our experience at Universidad de Buenos Aires - Castro, Marisa S. (2020)
The aim of this text, is to describe our teaching role in times of pandemic, recounting how we discovered strategies to teach in times of virtual presence, as well as the search for new experiences in teacher training, highlighting the importance of how we turn them into an opportunity for our self-improvement. Procedure: We will discuss the strengths and weaknesses that we found while we were going through this new path of online teaching, set up for the first time in the undergraduate courses of our University. Conclusion: The main educational accomplishments we achieved during the pandemic course were, to establish a true flipped classroom, and to use ludic strategies that were not common in our classes. On the other hand, we highlight the close contact we fulfilled with our students, which led them to recognize with high opinion our study methodology, the knowledge acquired, the strategies used, and our commitment and teaching predisposition.